ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN SUMBAWA - Pamungkas, Binar Dwiyanto; Utami, Sugita Julika (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the effectiveness and contribution of regional taxes on district own source revenue of Sumbawa District in 2012-2021. The type of this study was descriptif with a quantitative approach. The type of data used in this study was quantitative data obtained from secondary sources in the form of annual reports, documents and archives that have been published by the Central Statistics Agency (BPS) of Sumbawa District. Data collection in this study used documentation techniques. Data analysis in this study used Effectiveness and Contribution Analysis Techniques. The results of this study showed that the realization of regional tax revenue of Sumbawa District in 2012-2021 experienced fluctuating growth, but in general the performance of regional tax revenue of Sumbawa District over the last ten years was in the very effective category. These results showed that the regional government of Sumbawa District had very good capabilities in managing regional taxes so that the entire potential of the tax sector in the region can be optimized as a source of regional revenue. The contribution of regional tax on district own source revenue of Sumbawa District in 2012-2021 experienced fluctuating growth, but in general the contribution of regional taxes of Sumbawa District over the last ten years was in the medium category. These results showed that regional revenues from the tax sector have not been able to make a significant contribution to increasing district own source revenue (PAD) of Sumbawa District.